1980
DOI: 10.1128/iai.28.1.269-276.1980
|View full text |Cite
|
Sign up to set email alerts
|

Selective suppression of granuloma formation and delayed hypersensitivity in rabbits

Abstract: The relationship between dermal delayed hypersensitivity (DH) and granulomatous hypersensitivity was studied in rabbits sensitized with killed mycobacteria. Specific antigen challenge of sensitized animals resulted in extensive pulmonary granulomatous inflammation and induced suppression of both dermal DH and dermal granuloma formation. Whereas suppression of DH was concomitant with pulmonary granuloma formation, as is the case in a number of granulomatous diseases, a causal relationship between the two did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…More recently, the relationship between granuloma formation and delayed hypersensitivity was studied in our laboratory (51). The results of this study indicated that dermal delayed hypersensitivity and allergic granuloma formation in the skin are both suppressed in sensitized animals following systemic challenge with specific antigen.…”
Section: Immunodeficiency Associated With Infectious Diseasementioning
confidence: 82%
See 1 more Smart Citation
“…More recently, the relationship between granuloma formation and delayed hypersensitivity was studied in our laboratory (51). The results of this study indicated that dermal delayed hypersensitivity and allergic granuloma formation in the skin are both suppressed in sensitized animals following systemic challenge with specific antigen.…”
Section: Immunodeficiency Associated With Infectious Diseasementioning
confidence: 82%
“…Secondary immunodeficiency may be defined as a disorder affecting host defenses in *Department of Microbiology and Immunology, Bowman Gray School of Medicine, Winston-Salem, North Carolina 27103. February 1982 which the initiating factor arises outside of the immune system or is not restricted to immune elements. Secondary immune impairment occurs more frequently than primary immunodeficiency and commonly occurs in an older age group.…”
Section: Overviewmentioning
confidence: 99%